Differences in the clinical phenotype of adenomyosis and leiomyomas: a retrospective, questionnaire-based study - Böer, Bettina; Wallwiener, Markus; Rom, Joachim; Schoenfisch, Birgitt; Brucker, Sara Y.; Taran, Florin A. (Archives of gynecology and obstetrics, 2014)
To compare women undergoing laparoscopic hysterectomy with adenomyosis and women with leiomyomas.